Older adults are incapable of changing sensory-motor coupling during upright stance with visual manipulation and different attentional demands - Genoves, Giovanna Gracioli [UNESP]; Sanches, Caroline [UNESP]; Barela, José Angelo [UNESP] (Springer Nature, 2017)
Postural control functioning is characterized by adaptive adjustments, which involves several central nervous system centers. This study investigated the sensory-motor coupling in older and younger adults during concurrent different cognitive tasks while maintaining upright stance with visual manipulation. Fifteen older and 15 younger adults performed 9 trials of upright stance in a moving room. In the first trial, the room remained stationary. In the following 4 trials, the room oscillated but participants were not informed about visual manipulation and in two trials were required to countdown. In the last 4 trials, they were informed about the visual manipulation and were requested to resist to it and repeated the countdown twice again. Results indicated that older swayed with larger magnitude than younger adults. Visual manipulation induced correspondent sway in all participants and information and request to resist reduced visual influence only for young adults when they were not counting. These results suggest that sensory-motor coupling might be changed but requires attentional resources and young adults only achieve it. Differently, older adults are incapable of changing sensory-coupling that might be limited by the lack of attentional resources.
Keywords: Attention demand; Elderly; Postural control; Sensory-motor coupling; Visual